Does community-level social capital mitigate the impact of widowhood & living alone on depressive symptoms?: A prospective, multi-level study. (August 2020) - Nakagomi, Atsushi; Shiba, Koichiro; Hanazato, Masamichi; Kondo, Katsunori; Kawachi, Ichiro
Abstract: Widowhood and living alone are linked to increased risk of depression. We examined prospectively whether community-level social capital can mitigate the adverse impact of widowhood and living alone on depressive symptoms. We used data of the Japan Gerontological Evaluation Study of functionally independent adults aged 65 years or older. Three waves of surveys were collected in 2010, 2013 and 2016. We conducted gender-stratified multilevel linear regression to examine the moderating effects of community-level social capital on depressive symptoms (as assessed by the 15-point Geriatric Depression Scale) associated with widowhood and living alone. Widowhood in the past 12 months in combination with living alone was associated with a marked worsening in depressive symptoms among men (beta coefficient = 1.67; 95% confidence interval: 1.38, 1.95). Community-level civic participation, but not social cohesion or reciprocity, was associated with lower depressive symptoms in men and women. In addition, community-level civic participation moderated the association between depressive symptoms and recent widowhood/living alone among men (coefficient per 1 standard deviation = −0.30; 95% confidence interval: −0.59, −0.02). We found no significant effect modification of community-level social capital on depressive symptoms associated with widowhood and living alone among women. Communities with greater civic participation appear to mitigate the onset of depressive symptoms among recently widowed men living alone. Promotion of community activities might be an effective community-level intervention to promote mental health in this vulnerable group. Highlights: Recently widowed men living alone shows severe depressive symptoms. Social capital shows contextual associations with depressive symptoms. Lower depressive symptoms among people in communities rich in civic participation. Recently widowed men living alone benefit more from community civic participation.